Policy of Social Conflict Resolution: Implementation of the Malino Agreement in Maluku - Saidin Ernas (Jurnal Studi Pemerintahan, 2012)
Maluku conflict (Ambon) occurred in 1999 to 2003 is one of the most heartbreaking human tragedies in the history of Modern Indonesia. Various attempts have been made by the government to resolve the conflict, including by carrying out Malino Agreement for Maluku. This paper discusses the process of implementation of the Malino Agreement and analyzes the impact on the resolution of Maluku conflict. By using methods of descriptive analysis and a qualitative approach, this study can present some important findings. First, the Malino Agreement is one strategy (policy) to resolve SARA(racial) conflict well and democratically. It is seen from the atmosphere of the negotiation which is peaceful, honest and democratic. Parties had 11 points of peace agreement due to a strong desire to end the conflict in Maluku. Second, the Malino Agreement has brought positive impacst, i.e lack of escalation of conflict and violence in Maluku, even a year since the Malino Agreement, the peace has been enforced in Maluku. However, this paper also found that conflict resolution model such as Malino agreement still needs refinement, as Malino Agreement factually succeeded in pushing the cessation of conflict, but substantively has not resolved various problems that trigger conflicts in Maluku.